2019
DOI: 10.1021/jacs.9b01960
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Unfolding and Thermal Refolding of Single-Chain Nanoparticles Using Ligand–Metal Bonds

Abstract: Covalent macromolecules tend to fragment under mechanical stress through the mechanochemical scission of covalent bonds in the backbone. However, linear polymers that have been intramolecularly collapsed by covalent bonds show greater mechanochemical stability compared to other thermoplastics. Here, rhodium-π bonds are used for intramolecular collapse in order to show that mechanical stress can be removed from the polymer backbone and focused on weaker intramolecular cross-links, leading to polymer unfolding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 51 publications
2
61
0
2
Order By: Relevance
“…The results showed that addition of intramolecular CLs to linear polymer chains increases the polymer's resistance to fragmentation. Similarly to our previous studies, all the linear precursors ( L1 – L4 , which are all similar to each other), presented significant faster fragmentation rates compared to all SCPNs derived from them (see Tables ). That is true even when comparing the linear polymers to the least mechanochemically stable SCPNs, such as those folded by weak bonds like sulfide‐containing CLs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed that addition of intramolecular CLs to linear polymer chains increases the polymer's resistance to fragmentation. Similarly to our previous studies, all the linear precursors ( L1 – L4 , which are all similar to each other), presented significant faster fragmentation rates compared to all SCPNs derived from them (see Tables ). That is true even when comparing the linear polymers to the least mechanochemically stable SCPNs, such as those folded by weak bonds like sulfide‐containing CLs.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, the measured rates correlate well to the DFT prediction. CO bond is the strongest chemical bond and SCPN CL2‐2 is indeed undergoing slower mechanochemical fragmentation, given now the force induces a CC bond scission which may occur in the main chain instead of the crosslinker . Polymers folded by CLs with nothing but CC bonds undergo statistically faster fragmentation compared to those with CO CL ( CL2‐1 and CL2‐2 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The largest hurdle in the scale‐up of SCNP synthesis is currently the highly dilute concentrations of the intramolecular crosslinking, which prevent the development of strategies to produce SCNPs beyond the gram scale. As the desired intrachain reaction competes with the parasitic interchain reaction, concentrations <1 mg mL −1 are the current standard to achieve a selectivity for the intramolecular folding . Some examples require even lower concentrations of 0.02 mg mL −1 , 0.03 mg mL −1[17] or 0.04 mg mL −1 .…”
Section: Synthesis: Tackling the Scalabilitymentioning
confidence: 99%
“…In addition to light, mechanical fields are a trigger that enables high temporal control through immediate responses of the material. The group of Diesendruck recently reported a fascinating example of mechanically triggered SCNP unfolding (Figure ) . Based on the transition metal‐π interaction induced folding developed in the laboratory of Lemcoff, poly(butadienes) containing additional mechanophores where folded upon addition of rhodium(I)‐ethylene complexes.…”
Section: Function Beyond Catalytic Nanoreactorsmentioning
confidence: 99%
See 1 more Smart Citation